A Simulation Based Comparison of the Traditional Method, Rolling-6 Design and a Frequentist Version of the Continual Reassessment Method with Special Attention to Trial Duration in Pediatric Phase I Oncology Trials - Onar-Thomas, Arzu (2010)
The Traditional Method (TM), also known as the 3+3 up-and-down design, and the Continual Reassessment Method (CRM) are commonly used in Phase I Oncology Trials to identify the maximum tolerated dose (MTD). The Rolling-6 is a relative newcomer which was developed to shorten trial duration by minimizing the period of time during which the trial is closed to accrual for toxicity assessment. In this manuscript we have compared the performance of these three approaches via simulations not only with respect to the usual parameters such as overall toxicity, sample size and percentage of patients treated at doses above the MTD but also in terms of trial duration and the dose chosen as the MTD. Our results indicate that the toxicity rates are comparable across the three designs, but the TM and the Rolling-6 tend to treat a higher percentage of patients at doses below the MTD. With respect to trial duration, Rolling-6 leads to shorter trials compared to the TM but not compared to the CRM. Additionally, the doses identified as the MTD by the TM and the Rolling-6 differ in a large percentage of trials. Our results also indicate that the body surface area-based dosing used in pediatric trials can make a difference in dose escalation/de-escalation patterns in the CRM compared to the cases where such variations are not taken into account in the calculations, even leading to different MTDs in some cases.